Clinical features of the course of Rhinoviral infection in children - O. P. Popova; R. V. Vartanyan; S. V. Trushakova; S. V. Bunin; N. A. Dracheva (LLC "Diagnostics and Vaccines", 2021)
Acute respiratory viral infections remain the most common diseases in the world, accounting for about 90% of all infectious diseases. The possibilities of etiological decoding of ARVI using modern examination methods made it possible to establish an increase in the proportion of rhinovirus infection in the structure of ARVI.The aim of the study in this regard was to study the features of the clinical course of rhinovirus infection in children of different ages in modern conditions. The study included 50 patients with rhinovirus infection of children, among whom 1 2 children (24%) were under 1 year old; 34 children (68%) - 1-3 years old, 4 children (8%) - 3-7 years old. To confirm rhinovirus infection, a study of mucus from the nasopharynx by PCR was carried out.A thorough analysis of the symptom complex of the infection showed that in 1 3 (26%) patients the infectious process was limited to lesions of the upper respiratory tract, in 14 (28%) there were symptoms of acute stenosinglaryngotracheitis, in 1 1 (22%) children developed pneumonia, in 1 2 (24%) - bronchitis, with obstructive syndrome in 1 0 (83.3%) patients in this group.